Democracy and International Conflict - Alberto Vesperoni; Karl Wärneryd (Center for Economic Studies and ifo Institute (CESifo), 2016)
During the past two centuries, western nations have successively extended the voting franchise to citizens of lower income. We explain this process of democratization as a rational way for incumbent elites to wage war effectively on other nations, as in a strategic game of international conflict handing over military spending decisions to citizens who face a lower tax cost of arming may confer a strategic delegation advantage. We find supporting empirical evidence in case studies of franchise extensions in the United Kingdom, France, and the United States.
Keywords: D72; D74; F51; O15; 330; war; conflict; contest; democracy; franchise extension